Does school breakfast make a difference? An evaluation of an in-school breakfast programme in South Africa. (November 2016) - Hochfeld, Tessa; Graham, Lauren; Patel, Leila; Moodley, Jacqueline; Ross, Eleanor
Highlights: School-based nutritional programmes address the negative effects of nutritional deprivation on child development. School based breakfast feeding schemes are key social investments in human capital development. There was a reduction in numbers of overweight children and those reported as being stunted or wasted between baseline and follow up measurements. The breakfast scheme encouraged school attendance, reduced late coming, and improved concentration in class. The public-private partnership model warrants replication in other middle income countries. Abstract: This article describes an evaluation of an in-school breakfast feeding programme in Johannesburg, South Africa based on a public-private partnership. The purpose of the evaluation was to determine whether there were any changes in the anthropometric and school performance outcomes of children receiving the breakfast feeding programme. The evaluation included a three-phase approach to establish a baseline of learners in relation to performance and nutritional status; an interim phase; and final phase to ascertain any changes after the introduction of the breakfast programme. Triangulation of the anthropometric and qualitative research suggests that children benefitted from the public-private social investment scheme.